Survival of Neoadjuvant and Adjuvant Therapy Compared With Surgery Alone for Resectable Esophageal Squamous Cell Carcinoma: A Systemic Review and Network Meta-Analysis - Ma, Zeliang; Yuan, Meng; Bao, Yongxing; Wang, Yang; Men, Yu; Hui, Zhouguang (Frontiers in Oncology, 2021)
Objective: The optimal treatment for resectable esophageal squamous cell carcinoma (ESCC) remains controversial. Surgery is the primary treatment but with poor results. Attempts to improve patient survival have been made by introducing chemotherapy, radiotherapy, or both. However, randomized comparisons for all these strategies are not always available. This network meta-analysis compared the overall survival of neoadjuvant and adjuvant therapy compared with surgery alone to identify the most effective approach. Methods: We systematically searched electronic databases (PubMed, Embase, and Cochrane Library) for relevant studies published before April 2021. Only phase II and III randomized controlled trials comparing the following treatments were included: surgery alone, neoadjuvant chemotherapy (NCT), radiotherapy (NRT) or chemoradiotherapy (NCRT), adjuvant chemotherapy (ACT), radiotherapy (ART), or chemoradiotherapy (ACRT). The hazard ratios (HR) and 95% confidence intervals (CIs) of overall survival (OS) was identified as the measurement of effectiveness. A network meta-analysis was conducted to synthesize the evidence under the Bayesian framework, and the relative effects of all possible comparisons were made. The ranking analysis was performed to support the decision in clinical practice. Results: A total of 19 relevant trials comprising 3749 patients were identified. Compared with surgery alone, NCRT (HR 0.76, 95% CI 0.65-0.89) and NCT (HR 0.81, 95% CI 0.70-0.94) significantly improved OS, while other treatments, including NRT (HR 0.86, 95%CI 0.66-1.08), ACRT (HR 0.73, 95% CI 0.49-1.08), ACT (HR 0.96, 95% CI 0.75-1.21) and ART (HR 0.86, 95% CI 0.66-1.14), provided no significant survival advantage. None of the neoadjuvant and adjuvant treatments showed a statistically significant difference in OS to each other when compared in pairs. Conclusion: For resectable esophageal squamous cell carcinoma, this network meta-analysis showed that NCRT might be the optimal strategy, NCT may be the second choice, while other multimodality treatments may not improve OS compared with surgery alone.